Perinatal maternal factors influencing postpartum feeding practices at six weeks - Yanchi Wang; Kai Mao; Minjie Chu; Xiaopeng Lu (BMC, 2024)
Abstract Objective Despite the World Health Organization's recommendation of exclusive breastfeeding for the initial 6 months, breastfeeding rates decline within the first 6 weeks after delivery. This study aimed to (1) investigate the breastfeeding rate at 6 weeks postpartum and (2) explore the influence of perinatal factors on feeding patterns at 6 weeks postpartum. Method A total of 635 participants were enrolled from February to August 2023 at outpatient clinics in three tertiary hospitals in Nantong City. Variables were collected through questionnaires during the third trimester of pregnancy, including demographic information, pregnancy stress, anxiety, depression, sleep, and resilience. At 6 weeks postpartum, information regarding feeding patterns, delivery and postpartum situations, postpartum stress, anxiety, depression, sleep, and resilience was gathered. Initial single-factor analyses were conducted using feeding pattern as the dependent variable, and variables with significance were chosen as independent variables. The disordered multi-classification logistic regression model was then established using the stepwise forward method. Results Within the first 6 weeks, 35.28% (224/635) of postpartum women exclusively breastfed their infants. Factors influencing exclusive breastfeeding and formula feeding at 6 weeks postpartum included breast pain, sleep quality, mental resilience, difference between postpartum and late pregnancy anxiety, insufficient milk supply, and maternal herself caring for the infant (P < 0.05). Factors influencing the transition from exclusive to partial breastfeeding were insufficient milk supply and maternal herself caring for the infant (P < 0.05). Conclusion The study reveals a relative low rate of exclusive breastfeeding in China's first 6 weeks postpartum, along with a comparison of perinatal factors affecting three different feeding patterns. Our findings may contribute additional evidence to the association between perinatal factors and feeding patterns. This study guides healthcare professionals in developing strategies to promote exclusive breastfeeding and improve personalized counseling for exclusive breastfeeding and mental health.